2022
DOI: 10.1007/s00018-022-04314-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of choroid plexus development and its functions

Abstract: The choroid plexus (ChP) is an extensively vascularized tissue that protrudes into the brain ventricular system of all vertebrates. This highly specialized structure, consisting of the polarized epithelial sheet and underlying stroma, serves a spectrum of functions within the central nervous system (CNS), most notably the production of cerebrospinal fluid (CSF). The epithelial cells of the ChP have the competence to tightly modulate the biomolecule composition of CSF, which acts as a milieu functionally connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 143 publications
0
10
0
Order By: Relevance
“…72 Thus, we investigated morphology and gene expression of the choroid plexus (CP), since CP is the main source of CSF production. 73 We found that the macroscopic appearance of CPs isolated from Utx flox/flox and Utx Δ/Δ brains at E18.5 was almost similar (indicated by arrows in Figure S4A). Previous studies demonstrated that WNTand HES-related signaling pathways are essential in CP function.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…72 Thus, we investigated morphology and gene expression of the choroid plexus (CP), since CP is the main source of CSF production. 73 We found that the macroscopic appearance of CPs isolated from Utx flox/flox and Utx Δ/Δ brains at E18.5 was almost similar (indicated by arrows in Figure S4A). Previous studies demonstrated that WNTand HES-related signaling pathways are essential in CP function.…”
Section: Discussionmentioning
confidence: 80%
“…Ventriculomegaly can be caused by disordered homeostasis of cerebrospinal fluid (CSF) 72 . Thus, we investigated morphology and gene expression of the choroid plexus (CP), since CP is the main source of CSF production 73 . We found that the macroscopic appearance of CPs isolated from Utx flox/flox and Utx Δ/Δ brains at E18.5 was almost similar (indicated by arrows in Figure S4A).…”
Section: Discussionmentioning
confidence: 97%
“…The formation of liquid filled cavities in such induced conditions is observed after differentiation for more than 28 days and follows the appearance of characteristic cuboidal epithelium as has been shown in our study as well. As such, in our study the radiation impact mimicked the guided differentiation of CP organoids as judged also by the expression of CP markers such as AQP1, the water channel essential for CSF production and the tight junction proteins ZO1 and CLN3, which ensure the integrity of the CP 31 . While ZO1, even though being a more general marker of tight junctions, is found in neuroepithelial proliferation zones and in CP, the morphology of the latter is clearly distinguishable, rendering ZO1 a suitable marker for CP in addition to the others used in this study.…”
Section: Discussionmentioning
confidence: 74%
“…However, this process is rare and in our study occurred in less than 10% of all control organoids formed compared to up to 50–70% in irradiated organoids. Indeed, to generate CP organoids, dorsalization has to be induced using bone morphogenic protein (BMP) 4 24 that in vivo stimulates epithelial cell formation within the dorsal midline by repressing forkhead box (FOX) G1 31 , which supports neural stem/progenitor cell proliferation 32 . The formation of liquid filled cavities in such induced conditions is observed after differentiation for more than 28 days and follows the appearance of characteristic cuboidal epithelium as has been shown in our study as well.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of HSV DNA in the cerebrospinal fluid (CSF) serves as a gold standard test for HSE in the clinic, with a sensitivity of approximately 96% 6 . CSF is predominantly secreted by the choroid plexus (ChP), 7 which forms the blood–CSF barrier via tight junctions between adjacent epithelial cells and prevents the invasion of pathogens into CNS 8 . The ChP–CSF system is key to brain homeostasis, waste clearance, and immune regulations 9 .…”
Section: Introductionmentioning
confidence: 99%